Inhibition of CaMKII Phosphorylation of RyR2 prevents induction of atrial fibrillation in FKBP12.6 Knockout Mice - Li, Na; Voigt, Niels; Dobrev, Dobromir (Circulation research, 2012)
Rationale: Abnormal calcium release from sarcoplasmic reticulum (SR) is considered an important trigger of atrial fibrillation (AF). Whereas increased Ca2+/calmodulin-dependent protein kinase II (CaMKII) activity has been proposed to contribute to SR leak and AF induction, downstream targets of CaMKII remain controversial. Objective: To test the hypothesis that inhibition of CaMKII-phosphorylated type-2 ryanodine receptors (RyR2) prevents AF initiation in FKBP12.6-deficient (−/−) mice. Methods and Results: Mice lacking RyR2-stabilizing subunit FKBP12.6 had a higher incidence of spontaneous and pacing-induced AF compared with wild-type mice. Atrial myocytes from FKBP12.6−/− mice exhibited spontaneous Ca2+ waves (SCaWs) leading to Na+/Ca2+-exchanger activation and delayed afterdepolarizations (DADs). Mutation S2814A in RyR2, which inhibits CaMKII phosphorylation, reduced Ca2+ spark frequency, SR Ca2+ leak, and DADs in atrial myocytes from FKBP12.6−/−:S2814A mice compared with FKBP12.6−/− mice. Moreover, FKBP12.6−/−:S2814A mice exhibited a reduced susceptibility to inducible AF, whereas FKBP12.6−/−:S2808A mice were not protected from AF. Conclusions: FKBP12.6 mice exhibit AF caused by SR Ca2+ leak, Na+/Ca2+-exchanger activation, and DADs, which promote triggered activity. Genetic inhibition of RyR2-S2814 phosphorylation prevents AF induction in FKBP12.6−/− mice by suppressing SR Ca2+ leak and DADs. These results suggest suppression of RyR2-S2814 phosphorylation as a potential anti-AF therapeutic target.